DETERMINATION OF POLYCYCLIC AROMATIC HYDROCARBONS IN THE ICE CORE SAMPLES FROM GREENLAND - カワムラ, キミタカ; スズキ, イクコ; フジイ, ヨシユキ; ワタナベ, オキツグ; KAWAMURA, Kimitaka; SUZUKI, Ikuko; FUJII, Yoshiyuki; WATANABE, Okitsugu (National Institute of Polar Research, 1994)
P(論文) Polycyclic aromatic hydrocarbons (PAHs) were determined in the ice core samples taken from Greenland, Site-J (205 m long, ca. 450 years old) using a combined gas chromatography and mass spectrometry (GC-MS). More than forty PAHs ranging from naphthalene to benzo (ghi) perylene were detected in the ice samples. Phenanthrene, methylphenanthrene and dimethylphenan-threne were among major PAH species. Concentrations of total PAHs were low (av., 58 ng/kg-ice) before 1920 whereas they started to increase after the 1920s (av., 970 ng/kg-ice for the 1920s to 1980s) and gave the highest value (5800 ng/kg-ice) in the late 20th century. These trend is primarily explained in terms of an increased anthropogenic emission to the atmosphere from fossil fuel combustion in the northern hemisphere as well as atmospheric transport of the combustion-derived products over the Greenland ice sheet. This study demonstrated that PAHs are useful tracers to study atmospheric transport of anthro-pogenic pollutants and to reconstruct the historical trend of global air pollution. departmental bulletin paper